The evaluation of microbial air contamination in microbial pesticide manufacturing in bioreactors [Articol] - Yaroshevsky, V.; Osipenko, Tatyana; Yaroshevska, Julia (CEP USM, 2023)
The paper is dedicated to actual scientific and practical problem solutions for air treatment in microbial pesticide manufacturing. Experimental resultsof air filtration in series-link filters with 5 μm – 1 μm rating polypropylene cartridgesare shown. Obtained microbial contamination level of filtered air 3.4 CFU•m–3 was low and air quality seemed to be sufficient for fermentation broth aeration in the bioreactor. The reasons for such results and prospects of filtration system simplification for pilotscale microbial pesticide manufacturing are discussed.
Keywords: microbial pesticides; microbial air contamination; pollution; filtration